Knowledge, attitude and practice of adverse drug reaction reporting among healthcare professionals of a tertiary care hospital in Gujarat - Patel, Nirav N.; Patel, Devanshu J.; Desai, Haresh A. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: The objective of the present study was to assess knowledge, attitude and practice of adverse drug reaction reporting among healthcare professionals of Parul Sevashram Hospital, Parul University, Vadodara. Methods: The study was prospective, observational and questionnaire-based involving medical doctors, nurses and pharmacists of Parul Sevashram Hospital. A total number of 210 structured questionnaires were distributed among health care professionals (100 clinicians from various specialities, 100 nurses and 10 pharmacists). Written informed consent forms were obtained from participants as their consent to participate in the study. Results: All questionnaires were filled and returned producing overall response rate of 100%. 80% of the respondents were aware of the existence of Pharmacovigilance Program of India (PvPI). 90.95% and 91.90% of respondents felt ADR reporting is necessary and it would be beneficial to the patients respectively. Only 11.43% of respondents had reported ADRs. 90.95% and 85.24% of respondents suggested training is required in reporting ADR and regular information should be provided regarding ADR by PvPI respectively. Conclusions: The health care professionals had positive knowledge and attitude towards pharmacovigilance and there is a need to create awareness for better practice of ADR reporting. It would help to improve patient care.